IMPLEMENTATION OF THE CHILD IDENTITY CARD (KIA) ISSUANCE POLICY BY THE EAST BARITO DISTRICT POPULATION AND CIVIL REGISTRATION OFFICE, CENTRAL KALIMANTAN - Edy Susanto; Reno Affrian (International Journal of Business, Law and Political Science, 2026)
Objective:  This research aims to analyze the implementation of the Child Identity Card (KIA) issuance policy by the East Barito Regency Population and Civil Registration Office and to identify the factors influencing its success. Method: The research uses a qualitative approach with in-depth interviews, observation, and document study methods. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. Results: The research findings indicate that the implementation of the Maternal and Child Health (MCH) policy has been in accordance with the national regulatory framework, but has not been optimal in terms of socialization, human resources, service infrastructure, and community participation. Policy communication factors, implementation capacity, and societal conditions are the main determinants of implementation effectiveness. Novelty: The Child Identity Card (KIA) is a national policy aimed at providing official identification for children as part of fulfilling civil rights and population administration protection. The implementation of this policy at the local level faces various structural and contextual challenges, particularly in areas with limited geographical characteristics and institutional capacity, such as East Barito Regency. This research recommends strengthening socialization strategies, increasing the capacity of officials, and innovating cross-sectoral collaborative services to improve the coverage of KIA ownership in East Barito Regency.